Respuesta :

Let us take the 2nd equation.

x + 2z = 4

x = 4 - 2z

Let us substitute this value of x in equation 1.

5x + 2y + z = 4

5(4-2z) + 2y + z = 4

20 - 10z + 2y + z = 4

2y - 9z + 20 = 4

2y = 9z - 16

y = (9z - 16)/2

Let us substitute this value of y, as well as that of x that we used earlier, in the third equation.

2x + y - z = -1

2(4-2z) + (9z-16)/2 + z = -1

8 - 4z + (9z/2) - 8 + z = -1

Let us multiply both sides of this equation by 2.

16 - 8z + 9z - 16 + 2z = -2

3z = -2

z = [tex]\frac{-2}{3}[/tex]

x = 4 - 2z

  = 4 + [tex]\frac{4}{3}[/tex]

  = [tex]\frac{16}{3}[/tex]

y = (9z-16)/2

  = ([tex]\frac{-18}{3}[/tex] - 16)/2

  = ( [tex]\frac{-66}{3}[/tex])/2

  = -22/2

  = -11

Therefore, x = [tex]\frac{16}{3}[/tex], y = -11, and z = [tex]\frac{-2}{3}[/tex].